Teaching in Blended Learning Environments: Creating and Sustaining Communities of Inquiry - Norman D. Vaughan, Martha Cleveland-Innes, and D. Randy Garrison (Issues in Distance Education, 2013)
Teaching in Blended Learning Environments provides a coherent framework in which to explore the transformative concept of blended learningÑthe organic integration of complementary face-to-face and online approaches and technologies. Built upon the theoretical framework of the Community of InquiryÑthe premise that higher education is both a collaborative and individually constructivist learning experienceÑthe authors present seven principles for harnessing the opportunities for teaching and learning available through technology. Focusing on teaching practices related to the design, facilitation, direction, and assessment of blended learning experiences, this text addresses the growing demand for improved teaching in higher education.